Pengaruh Sanksi Pajak dan Sosialisasi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi: Studi Kasus di KPP Pratama Serpong - Fabian, Fransiskus Reynald Ivan; Sunanto, Ghea. B. Astrid (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2025)
This study was conducted to analyze the influence of tax sanctions and tax socialization on taxpayer compliance at the Serpong Pratama Tax Office (KPP Pratama Serpong), considering the low formal compliance ratio that has not yet reached the national target. The main objective of this study is to answer whether tax sanctions and tax socialization have a partial or simultaneous effect on taxpayer compliance. This study uses an associative quantitative method. The population in this study were 50,020 individual taxpayers registered at the Serpong Pratama Tax Office (KPP Pratama Serpong) and with the Slovin formula, a sample of 100 respondents was obtained using accidental sampling techniques and data collection through questionnaires. The data analysis techniques used were validity tests, reliability tests, classical assumption tests, descriptive analysis, multiple regression tests, hypothesis tests and coefficient of determination tests. The results of the study indicate that both partially and together, tax sanctions and tax socialization have a positive effect on individual taxpayer compliance at the Serpong Pratama Tax Office. The coefficient of determination of 35% indicates that the contribution of the two determinants to taxpayer compliance is 35% and the remaining 65% (100-35)% is influenced by other factors not studied.